THE EFFECT OF COMPENSATION AND MOTIVATION TO EMPLOYEE PERFORMANCE - Asriani, Asriani; Lorensa, Devia; Saputri, Febrida; Hidayati, Tetra (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
The success of a company is influenced by employee performance. By improving employee performance will make it easier for company goals to be achieved. One factor that can improve employee performance is the provision of compensation and motivation. This study aims to determine and analyze the effect of compensation and work motivation on employee performance. The sampling technique used is by taking a purposive sampling. The method used in this research is data collection through questionnaires, literature study, and observation. The technique used to analyze simple linear regression data and examine hypotheses simultaneously and partially. The result is compensation and motivation significantly influence employee performance simultaneously.